Effect of black seed fiber, on the physical, thermal, mechanical, morphological, and biodegradation properties of cornstarch-based biocomposites - Abotbina, Walid; Sapuan, S. M.; Sultan, M. T. H.; Alkbir, M. F. M.; Ilyas, R. A. (Springer, 2023)
This work aims to investigate the effect of black seed fiber as a reinforcing material for the fabrication of cornstarch-based biocomposite. The casting procedure was applied to fabricate the biocomposite at different concentrations of black seed fiber (3%, 6%, and 9%) and plasticizer mixture of fructose and glycerol set at a proportion of 30% (1:1) for total weight. The biocomposite films were tested in terms of casting procedure physical, tensile, thermal, and morphological properties. Increasing the black seed fiber concentration from 3% to 9% decreased the density and moisture content of the films by 15.67% and 29.04%, respectively, and soil burial tests showed that the films became less resistant to biodegradation. On the other hand, an increase in tensile strength (40%), Young’s modulus (26%), and crystallinity index (64%) were observed when 9% of black seed fiber was added, reflected in a consistent structure and outstanding matrix-reinforcement compatibility. It was also found that reinforced biocomposite exhibited better thermal stability and more intermolecular hydrogen bonding compared to the control film. Overall, the addition of black seed fiber as promising reinforcing material significantly improved the performance of the films, which may contribute to the development of the biopolymers industry in response to both community needs and environmental issues.